2011
DOI: 10.1264/jsme2.me10152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-Acetyl-D-Glucosamine on Gene Expression in Vibrio parahaemolyticus

Abstract: We analyzed the effect of N-acetyl-D-glucosamine (GlcNAc) on gene expression in the marine bacterium Vibrio parahaemolyticus. The total number of genes whose expression was induced and repressed genes in the presence of GlcNAc was 81 and 55, respectively. The induced genes encoded a variety of products, including proteins related to energy metabolism (e.g. GlcNAc and chitin utilization), transport, central metabolism and chemotaxis, hypothetical proteins, mannose-sensitive hemagglutinin pilus (MSHA), and a Pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…UDPG can be used as a precursor of polysaccharides such as exopolysaccharide (EPS), which are important to maintaining biofilms of Staphylococcus epidermidis, Vibrio parahaemolyticus, and A. baumannii [9], [21], [22]. In particular, proteome data on A. baumannii biofilm cells indicated that EPS matrix formation occurs via the Leloir pathway [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UDPG can be used as a precursor of polysaccharides such as exopolysaccharide (EPS), which are important to maintaining biofilms of Staphylococcus epidermidis, Vibrio parahaemolyticus, and A. baumannii [9], [21], [22]. In particular, proteome data on A. baumannii biofilm cells indicated that EPS matrix formation occurs via the Leloir pathway [23].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, N -acetyl-D-glucosamine (GlcNAc) appears to influence a variety of cellular processes, including energy metabolism, chitin utilization, competence, biofilm formation and pathogenicity in bacteria [22]. For example, a homopolymer of GlcNAc is located on the cell surfaces of Staphylococcus epidermidis and S. aureus , where it serves as an essential factor for biofilm formation [21], [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transcriptional evidence that the V. fischeri population in the mature squid light‐organ symbiosis is exposed to chitin as a nutrient has been supported by the discovery of host blood cells carrying particulate chitin in the tissue surrounding the symbionts (Heath‐Heckman and McFall‐Ngai, 2011). In addition, for both V. cholerae and V. parahaemolyticus , exposure to GlcNAc leads to the induction of genes associated with GlcNAc utilization (Meibom et al ., 2004; Thompson et al ., 2011). Recently, the nagA and nagB genes have been implicated in having an impact on host colonization by V. cholerae (Ghosh et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The genes encoding these enzymes are under the control of the same system, known as the nag regulon. Some studies have examined this gene cluster (21,22), and there are reports of chitin-derived sugars inducing the expression of these genes (13,23). nagE, nagA, nagC, and nagB correspond to the N-acetylglucosamine-specific IIABC component (VP0831), N-acetylglucosamine-6-phosphate deacetylase (VP0829), the N-acetylglucosamine repressor (VP0828), and glucosamine-6-phosphate deaminase (VPA0038), respectively.…”
Section: Discussionmentioning
confidence: 99%